Využití matematických metod při tvorbě investičního portfolia - Holub, Miroslav (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2021)
The bachelor thesis is focused on the use of mathematical methods in creating an investment portfolio, which is designed for small investor. The theoretical part of the thesis describes the necessary knowledge to understand Markowitz model, selected indicators of financial analysis and the Value at Risk method. The practical part contains a selection of investment instruments traded on the US market according to established criteria, the creation of a real portfolio of these investment instruments and the final evaluation of results.
Keywords: Markowitz model; Markowitzův model; Sharp ratio; Efektivní množina; finanční analýza; Value at Risk; Financial analysis; Efficient frontier; Sharpeho poměr